An Early Viral Response Predicts the Virological Response to Ribavirin in Hepatitis E Virus Organ Transplant Patients. Issue 10 (October 2015) - Kamar, Nassim; Lhomme, Sebastien; Abravanel, Florence; Cointault, Olivier; Esposito, Laure; Cardeau-Desangles, Isabelle; Del Bello, Arnaud; Dörr, Gaëlle; Lavayssière, Laurence; Nogier, Marie Béatrice; Guitard, Joelle; Ribes, David; et al.
<x xml:space="preserve">Abstract</x> Background Ribavirin is efficient at treating chronic hepatitis E virus infection in solid-organ transplant patients. However, the early kinetics of viral replication under therapy and the impact of immunosuppressant regimens on viral replication are unknown: thus, determining the aim of our study. Methods Thirty-five patients with a solid-organ transplant and chronic hepatitis E virus infection were given ribavirin for 3 months. The hepatitis E virus (HEV) RNA concentrations were determined before treatment, at days 7, 15, and 21 and at months 1, 2, and 3 during therapy and after ribavirin cessation. Results A sustained virological response (SVR) occurred in 63%. Decreased viral concentration within the first week post-ribavirin therapy was an independent predictive factor for SVR, and a decreased HEV concentration of 0.5 log copies/mL or greater had an 88% positive predictive value. No correlation between ribavirin trough level on day 7 or at month 2 with a virological response or an SVR was observed. Before therapy, HEV RNA concentration was significantly greater in patients receiving mechanistic target of rapamycin inhibitor-based immunosuppression compared to patients given calcineurin inhibitors. The use of mycophenolic acid did not impact on the response to ribavirin. Conclusion An early response to ribavirin can be used to define the optimal duration of therapy in the setting of HEV infection.